ANALISIS KINERJA: TRAINING, LINGKUNGAN KERJA, BUDAYA ORGANISASI DAN KEPUASAN KERJA - Rifan Prasetyo; Titik Nurbiyati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
The purpose of this study is to test training, employee environment, and organizational culture on employee performance with satisfaction as an intervening variable. using a quantitative approach, the data of this study were collected from 100 employees Sekretariat Badan Pelatihan dan Pendidikan Keuangan Jakarta. The sampling technique used was random sampling. Partial Least Square (PLS) is used to test the hypothesis in this study by using SmartPLS 3.0. The results of this study found that there is a significant positive effect of training on employee performance, there is a significant positive effect of the work environment on employee performance, and there is a significant positive effect of organizational culture on employee performance. then, there is a significant positive effect on job satisfaction, there is a work environment that has a significant positive effect on job satisfaction, there is a significant positive organizational culture on job satisfaction, and there is a positive job satisfaction on employee performance. besides, it was found that the direct effect of training on employee performance was greater than the indirect effect of training on job satisfaction, there was a work environment that directly affected employee performance greater than the indirect influence of the work environment on job satisfaction, and there was an influential organizational culture directly on employee performance is greater than the indirect influence of organizational culture on job satisfaction.